2017
DOI: 10.1007/s13205-017-0986-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanoformulation of Leonotis leonurus to improve its bioavailability as a potential antidiabetic drug

Abstract: Nanostructured lipid carriers (NLCs) of were successfully produced using high-pressure homogenisation (HPH) on a LAB 40 homogeniser. The particle size was determined for the formulation as well as short-term stability study. The formulation was exposed to Chang liver cells for a glucose uptake study and to INS-1 cells for a chronic insulin release study under normoglycaemic and hyperglycaemic conditions. The particle size of the extract NLC was 220 nm with a PdI of 0.08 after homogenisation at 800 bar. The for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Under hyperglycemic condition, the nanoformulation stimulated insulin release in INS1 pancreatic β cells and elevated glucose uptake in Chang liver cells compared to the extract. Extract-loaded NPs had an average particle size of 220 nm and were stable in different storage temperatures (Odei-Addo et al, 2017). Therefore, NLCs might be a suitable candidate to be evaluated in an animal model of diabetes.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Under hyperglycemic condition, the nanoformulation stimulated insulin release in INS1 pancreatic β cells and elevated glucose uptake in Chang liver cells compared to the extract. Extract-loaded NPs had an average particle size of 220 nm and were stable in different storage temperatures (Odei-Addo et al, 2017). Therefore, NLCs might be a suitable candidate to be evaluated in an animal model of diabetes.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…They present high tolerability and application in sensitive routes of administration, such as intravenous and ocular. They are obtained by high‐pressure homogenization techniques, hot or cold, ultrasound, and emulsification with solvent and microemulsion methods [19,54] …”
Section: Obtaining Nanosystemsmentioning
confidence: 99%
“…They are obtained by high-pressure homogenization techniques, hot or cold, ultrasound, and emulsification with solvent and microemulsion methods. [19,54] There are, as we can observe, ample and diversified obtaining techniques with particular methodologies, with attention to the best way of incorporating natural actives and maintaining the stability of the final product. This way, it is important to understand the importance of the techniques for therapeutic, food, and cosmetic purposes, according to the potential of the extracts of the vegetable species.…”
Section: Obtaining Nanosystemsmentioning
confidence: 99%
“…The pharmacology of L. leonurus is well-recorded as reviewed by Mazimba (2015) [ 140 ] and Nsuala et al (2015) [ 10 ], though some notable studies include the in vitro anti-HIV activity of several South African medicinal plant extracts, of which L. leonurus was recorded to exhibit significant HIV-1 inhibition (33% reduction in HIV-1 p24, p < 0.05) [ 352 ]. Other studies have observed noteworthy anti-inflammatory and analgesic activity [ 137 ], as well as anthelmintic [ 353 , 354 ], hepatoprotective [ 137 ] and anti-diabetic activities [ 355 ]. Furthermore, the presence of marrubiin in several Lamiaceae species and the pharmacological efficacy of this terpenoid has been well documented.…”
Section: Traditional Usesmentioning
confidence: 99%